Investigation of the effects of different ink density values on color gamut in offset printing - Tutak, Dogan; N. Beytut, Huseyin; Ozcan, Arif (Journal of Graphic Engineering and Design, 2018)
A standard color gamut can be obtained with CMYK samples that are printed with an offset printing system according to the ISO 12647-2:2013. It is possible to enhance or widen the color gamut during the printing process by interfering with the density and dot gain characteristics. Printing with a wider color gamut provides a more vivid area and more depth in color. In this study, print trials were conducted at first with standard values (density, dot gain and such). Then another trial was conducted by changing the density values respectively during the trial. Ink density values for all colors were decreased from the standard value as -0.15D, -0.30D and then increased as +0.15D, +0.30D. Color gamuts of the trials were calculated and compared at the end. It is found that ink density values directly affect color gamut in offset printing. It is also found that the color gamut decreases equally when ink density values decrease and vice versa. However, some printing problems occurred with high density values even though it gave an expanded color.